An optimised chromatin immunoprecipitation (ChIP) method for starchy leaves of Nicotiana benthamiana to study histone modifications of an allotetraploid plant - Ranawaka, Buddhini (Mol Biol Rep, 2020)
All flowering plants have evolved through multiple rounds of polyploidy throughout the evolutionary process. Intergenomic interactions between subgenomes in polyploid plants are predicted to induce chromatin modifications such as histone modifications to regulate expression of gene homoeologs. Nicotiana benthamiana is an ancient allotetraploid plant with ecotypes collected from climatically diverse regions of Australia. Studying the chromatin landscape of this unique collection will likely shed light on the importance of chromatin modifications in gene regulation in polyploids as well its implications in adaptation of plants in environmentally diverse conditions. Generally, chromatin immunoprecipitation and high throughput DNA sequencing (ChIP-seq) is used to study chromatin modifications. However, due to the starchy nature of mature N. benthamiana leaves, previously published protocols were unsuitable. The higher amounts of starch in leaves that co-precipitated with nuclei hindered downstream processing of DNA. Here we present an optimised ChIP protocol for N. benthamiana leaves to facilitate comparison of chromatin modifications in two closely related ecotypes. Several steps of ChIP were optimised including tissue harvesting, nuclei isolation, nuclei storage, DNA shearing and DNA recovery. Commonly available antibodies targeting histone 3 lysine 4 trimethylation (H3K4me3) and histone 3 lysine 9 dimethylation (H3K9me2) histone modifications were used and success of ChIP was confirmed by PCR and next generation sequencing. Collectively, our optimised method is the first comprehensive ChIP method for mature starchy leaves of N. benthamiana to enable studies of chromatin landscape at the genome-wide scale. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11033-020-06013-1) contains supplementary material, which is available to authorized users.